Maize stalk as reinforcement in natural rubber composites - Chigondo, Fidelis; Shoko, Piwai; Nyamunda, Benias C.; Guyo, Upenyu; Moyo, Mambo (IJSTR, 2016)
Maize stalk fibres can be used as fillers in natural rubber composites replacing expensive and non- iodegradable inorganic fillers. Maize stalk fibres were chemically modified with acetic anhydride (acetylation) to enhance their compatibility with the hydrophobic rubber polymer matrix. The fibre was characterised using FTIR showing a spectrum with a well defined peak at 1742 cm-1 (attributed to the carbonyl groups –C=O), indicating that new acetyl groups were introduced to cellulose. The curing and physico–mechanical properties of the composite as a function of filler loading was determined and compared with the values obtained using commercial grade hydrated silica. The natural rubber-maize stalk filled composites showed good processing safety in terms of torques and scorch. Compared with untreated maize-natural rubber composites, the acetylated composites exhibited higher mechanical properties, reduced moisture absorption and higher resistant to hydrothermal aging. Based on mechanical properties and statistical treatment of data, composites filled with 20 phr treated maize stalk had the optimum set of mechanical properties (tensile strength of 22.4 MPa, elongation at break 404 % and hardness Shore A of 55) that were closely comparable with commercial hydrated silica filled composites. Maize stalk has therefore demonstrated its potential to be used to reinforce natural rubber for shoe sole production.